Early activation of CD95 is limited and localized to the cytotoxic synapse - Sánchez, María; Gülcüler Balta, Gülce Sıla (The FEBS journal, 2018)
The cytotoxic synapse formed between cytotoxic T lymphocytes or natural killer cells expressing CD95L and target cells with CD95 on their surface is a key pathway for apoptosis induction by the immune system. Despite similarities with the immune synapse in antigen presenting cells, little is known about the role of the spatiotemporal organization of agonistic proteins/receptor interactions for CD95 signaling. Here, we have developed an artificial cytotoxic synapse to examine how mobility and geometry of an anti-CD95 agonistic antibody affect receptor aggregation and mobility, ie the first step of receptor activation. By measuring the distribution, diffusion coefficient, and fraction of immobile CD95 receptor in living cells, we show that at short times, the initial activation of CD95 occurs locally and is limited to the contact region of the cytotoxic synapse. This anisotropic activation of apoptotic signaling supports a role for confined interactions on the efficiency of signal transduction that may have implications for biomedical applications of extrinsic apoptosis induction.
Gesehen am 15.05.2020